DIDACTIC REQUIREMENTS FOR ORGANIZING LABORATORY WORKSHOPS IN PHYSIOLOGY IN HIGHER EDUCATIONAL INSTITUTIONS - Tursinboyeva Halima Otabekovna (Modern American Journals, 2025)
This article presents the didactic requirements for organizing laboratory classes in physiology in higher education institutions, their current state and some parts of the ways to eliminate them.
Keywords: Didactics, laboratory, teaching, learning, training, method, tool, result, special didactics, general didactics